A research update on the antitumor effects of active components of Chinese medicine ChanSu - Jia, Jinhao; Li, Jie; Zheng, Qiusheng; Li, Defang (Frontiers in Oncology, 2022)
With the development of economy worldwide and the continuous improvement of people’s living standards as well as increased life stress, the incidence and mortality rates of cancer are also rising continuously. As the second most common cause of death globally, cancer has become an ongoing public health challenge worldwide. When chemotherapeutic drugs cannot generate satisfactory outcomes, the search for effective cancer treatment regimens becomes imperative. The extensive clinical application of traditional Chinese medicine may suggest a new direction to combat cancer, and the therapeutic effects of active ingredients from Chinese herbal medicine on cancer are now being widely studied in the medical community. As a traditional anticancer Chinese medicine, Chansu has been clinically applied since the 1980s and has achieved excellent antitumor efficacy. Cinobufacini injection, a natural antineoplastic drug, is also broadly used in clinical practice. Many pharmaceutical scientists have investigated the anticancer mechanisms of Chansu and obtained certain research progress. This article reviews the research progress and antitumor mechanisms of action of Chansu active components and proposes that multiple active components of Chansu may be potential anticancer drugs.